PELAYANAN ADMINISTRASI KEPENDUDUKAN PASCA KONFLIK LIMA DESA DI KABUPATEN KAMPAR - Situmeang, Debora; Mashur, Dadang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The background of this research is the expansion of a region which caused the change of territorial boundaries, and the boundaries of the territory are not clearly defined. Unclear regional boundaries can trigger conflicts in border areas and hinder the implementation of local government functions. The conflicts are also made the society of five villages feel confused because of the dualism of leadership in the local government which is from Kampar regency and Rokan Hulu regency. The society is very disadvantaged with the conflicts. The objectives of this research are (1) to find out the post-conflict public administration service of the five villages in Kampar regency, (2) to know the factors affecting the post-conflict public administration service of the five villages in Kampar regency.The theoretical concepts used by the researcher are Carson and Schwarz's service theory in Denhard; which uses the indicators of Comvenince (convenience), Security, Reliability, Personal Attention, Problem Solving Approach, Faireness ( justice), fiscal responsibility and citizen influence. This study used descriptive qualitative method.The result of this research is that the post-conflict population administration service of five villages in Kampar regency has not run optimally. This can be seen from the indicators used by the researcher. The things that has not been done well is The citizen influence where the society in the area is less aware or less understand that they can affect the quality of government service. An approach to the society is needed to enable them understand the conflict and the importance of taking care their administration data , so that their status as a citizen is clear. The influencing factors based on the researcher study are facilities, infrastructure, employee discipline and road access.Keywords: Service, Public administration